2022
DOI: 10.1021/acs.macromol.1c02604
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Polyethylene Molecular Weight Distributions Using Catalyst Support Composition

Abstract: Bimodal polyethylene is generated from a single immobilized catalyst on a single support under a single set of reaction conditions without introducing chain transfer agents. Using rac-ethylene­bis­(1-indenyl)­zirconium dichloride [(EBI)­ZrCl2] immobilized on a nickel-containing layered double hydroxide (LDH) support produces two distinct molecular weight distributions. The ratio of these two distinct fractions can be tuned by varying the LDH support as well as by changing the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Other studies reported the application of LDH-supported metallocene catalysts for ethylene polymerization. [12,36,35] Kenyon et al reported the LDH-supported catalysts, thereby paying more attention to catalyst immobilization and tuning polyethylene properties. [36] In another study by Kenyon et al, the effect of LDH composition on the catalytic performance of metallocene was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported the application of LDH-supported metallocene catalysts for ethylene polymerization. [12,36,35] Kenyon et al reported the LDH-supported catalysts, thereby paying more attention to catalyst immobilization and tuning polyethylene properties. [36] In another study by Kenyon et al, the effect of LDH composition on the catalytic performance of metallocene was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1‐4 ] However, efficient methods to precisely tune the polymer MWD in cationic polymerization haven't been well explored, which is essential for polymer properties such as mechanical properties, crystallization behavior, and viscoelasticity. [ 5‐7 ] In fact, it was until recent years some efficient strategies to tune polymer MWD have been developed such as metered additions of initiating species in controlled polymerization, [ 8‐9 ] blending polymers directly, [ 10‐12 ] or through combination with flow chemistry, [ 13‐18 ] tuning the components of the polymerization systems, [ 19‐26 ] and adjusting the external stimulus. [ 27‐34 ] In terms of cationic polymerization, Aoshima et al .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…For that reason, layered double hydroxides (LDHs), one family of the most promising solid bases with two-dimensional, ion-intercalated, anisotropic layered structure have attracted significant interest. [38][39][40][41] These anionic clays consist of octahedrally coordinated metal hydroxide layers in which the bivalent cations are partially substituted by trivalent cations, generally. 42,43 As a result of the isomorphous substitution, the hydroxide layers are positively charged which is compensated by the interlamellar, solvated anions.…”
Section: Introductionmentioning
confidence: 99%